Notes about digital education in democracy and education about the European Union - Silva, Maria Manuela Magalhães (2021)
Digitalization can be defined as a socio-technical process of applying digitalization techniques in social and institutional contexts that make digital technologies infrastructural. The context of increasing digitalization and connection of the real world to the digital world has led to changes in people everyday lives, markets, business relationships and value chains. Education accompanies and adapts to the new digital age. Digital education is a political intention. But is it already a reality? The pandemic situation outbreak of COVID-19 in 2020 came, suddenly, to put the use of technologies at an immediate and high level, but perhaps without full preparation. This unexpected use demonstrates the imperative need for concerted action to guarantee conscious and democratic access. If education values digital, another question arises as how to use the new ways to achieve a priority for the European Union: education about the European Union. It seems so obvious and simple and it is still so fragile and scattered. European literacy is still a skill to be acquired at a minimum level for most of the population in the Member States, as known by the Commission. In this context, it is intended to debate the valuation of the European Union's intentions in achieving access to digital media for education. This study, based on the literature review methodology, intends to look at the legislative and preparatory documents and cases presented in the literature that consecrate the issue of digital education. For this purpose, an integrative literature review will be used. Theoretical-academic, it is consolidated through systematic and methodologically selected normative interpretation of national, international legal texts and European Union law.